Mind the app: Do European deposits react to digitalisation? - Luisa Fascione; Juan Ignacio Jacoubian; Beatrice Scheubel; Livio Stracca; Nadya Wildmann (European Central Bank (ECB), 2025)
The March 2023 banking turmoil has intensified discussions whether social media and the digitalisation of finance have become significant factors in driving severe deposit outflows. We introduce the concept of deposits-at-risk and utilize quantile regressions for disentangling determinants of stressed outflows at the lowest tail of the distribution. For a sample of large banks directly supervised by the ECB, our findings indicate that an increased use of online banking services leads to a small amplification of extreme deposit outflows, but this effect is not further exacerbated by the availability of a mobile banking app. Online banking use and availability of a mobile app do not have a causal effect on deposit volatility in normal times. Finally, social media are impactful only in idiosyncratic cases.
Keywords: G20; G21; G28; 330; liquidity risk; deposit outflows; bank runs; banking regulation